Hydrodynamic Pressure Gradient Correlation of Some Iraqi Oil Wells - HAZIM FAWZI, RIYADH (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
Empirical equation has been presented to predict the optimum hydrodynamicpressure gradient with optimum mud flow rate (one equation) of five Iraqi oil wellsto obtain the optimum carrying capacity of the drilling fluid ( optimum transportcuttings from the hole to the surface through the annulus).This equation is a function of mud flow rate, mud density and penetrationrate without using any charts or graphs.The correlation coefficient accuracy is more than 0.9999.